Bantuan Spiritual Untuk Meningkatkan Ibadah Pasien Stroke Dengan Pendekatan Budaya Lokal Selama Di Rawat Inap - Ahmad Zaini Arif; Faridatul Istibsaroh; Dessy Rindiyanti Harista (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Background: A person with a stroke has a functional disorder of the brain in the form of nerve paralysis (deficit neurologic). Besides having physical and psychological problems as well as spiritual problems, namely prayer is often experienced in stroke patients.Objective: The Influence of Spiritual Assistance With Local Cultural Approaches Towards Worship Of Stroke Patients While In HospitalizationMethods: This study uses the quasi-experimental design with the Pre Post Test Control Group Design approach. Intervents are given with a duration of 45-60 minutes in 1 meeting held for 3 meetings. The number of samples in this study was 18 samples of intervention groups and 18 samples of control groups at Dr. Mohammad Zyn Hospital in Sampang Regency with simple random sampling techniques with Islamic inclusion criteria, vital signs stable, temperatures 36-38 ° C; pulse 60-00 times per minute, breathing 16-24 times per minute, compositional awareness of GCS scores (14-15).Results: The results of the non-parametric test, namely the Wilcoxon test, obtained a value of P = 0.000, meaning that there is an influence of spiritual assistance with a local cultural approach to the worship of stroke patients while in hospital. Providing spiritual support with a local cultural approach can increase the implementation of patient worship during hospitalization in hospitals so that nurses can provide and increase spiritual nursing careConclusion: Providing spiritual support with a local cultural approach can increase the implementation of patient worship during hospitalization in hospitals so that nurses can provide and increase spiritual nursing care